Inhibition of TNF-α and JNK Signaling Pathway Can Reduce Paclitaxel-Induced Apoptosis of Mouse Cardiomyocytes - Shuang Ren; Tianwen Huang; Danyan Ou; Luhuai Feng; Sisi Huang; Chaonan Zhou; Lianying Ge (Applied Bionics and Biomechanics)
Paclitaxel (PTX) is a widely used chemotherapeutic drug for treating tumors. However, studies have shown that it can cause cardiac problems such as arrhythmia, myocarditis, chronic cardiomyopathy, and heart failure. Therefore, it is essential to study the mechanism behind the cardiotoxicity of PTX in tumor treatment. In this study, we initially injected PTX into mice to establish a myocardial cell apoptosis model to observe the degree of damage to mouse myocardium caused by PTX. Upon determining the levels of mouse myocardial creatine phosphokinase (CK), myokinase isoenzyme (CK-MB), aspartate transaminase (AST), and lactate dehydrogenase (LDH), we found that all of these levels showed apparent increases in mice treated with PTX. Further analyses of the TNF-α level and the expression of Jun N-terminal kinase (JNK) and Bcl-2 family-related proteins in myocardial tissue were performed. It was found that PTX increased the protein levels of TNF-α, Bax, p-JNK, and JNK in myocardial tissue but decreased the protein level of Bcl-2. After 1 month of PTX treatment in mice, we inhibited the expression of TNF-α and JNK proteins, which reduced the effect of paclitaxel on the apoptosis of mouse cardiomyocytes. The protein levels of Bax, p-JNK, and TNF-α in cardiomyocytes were reduced, while there was a relative increase in the Bcl-2 protein level. The findings suggested that inhibition of the NK signaling pathway and TNF-α can lessen the effect of PTX on mouse cardiomyocytes.